Efek Pemberian Pupuk Hayati VP3 yang Diperkaya Trichoderma viride FRP3 terhadap Total Populasi Mikroorganisme Tanah dan Pertumbuhan Tanaman Kedelai (Glycine max (L) Merrill) - Feby Syaharani; Siti Muslikah; Novi Arfarita (Universitas Islam Malang, 2022)
Biofertilizer is a living microorganism material and is useful for increasing soil fertility and the production quality of a plant. The VP3 biofertilizer formulation is known to increase the activity of beneficial microorganisms for plant growth. Trichoderma viride is a good microorganism used as a biopesticide. This study was conducted to determine the effect of VP3 and Trichoderma viride FRP3 biofertilizers on the growth of soybean (Glycine max (L) Merrill) and the total population of soil microorganisms. This research was conducted in the greenhouse of the Faculty of Agriculture and the Halal Center Intedrated Laboratory of Microbiology, Islamic University of Malang. This study used a simple Randomized Block Design (RAK) with 7 treatments with 3 replications. The results of the data analysis using the analysis of variance with the F test with a significance level of 5%, if there was a significant effect between treatments, it was continued with the BNT 5% if there was a significant effect. The results showed that treatment N had the highest average yield for soybean plant growth.